2011
DOI: 10.1002/mds.23501
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and compulsivity in drug‐naïve patients with Parkinson's disease

Abstract: Similar to our healthy control population, we found a significant proportion of early PD patients positive for ICDs before starting treatment. We also found a relationship between impulsivity and depression. A detailed behavioral assessment before starting dopaminergic therapy is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 26 publications
11
96
0
4
Order By: Relevance
“…It has been validated for use in children/adolescents (Cosi et al., 2008; Hartmann et al., 2011; Li & Chen, 2007; von Diemen et al., 2007) and among elderly (Tamam, Bican, & Keskin, 2014). BIS‐11 has also been used among PD patients Antonini et al, 2011; Smulders et al, 2014 among patients with depression (Lu et al., 2012; reviewed in Saddichha & Schuetz, 2014) as well as in combinations of both (Fonoff et al., 2015). ICDs have also been studied (binge eating: [Akkermann et al, 2010], substance dependence: [Gülec et al., 2008], prison inmates: [Patton et al., 1995], elderly with ICDs: [Tamam et al., 2014]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been validated for use in children/adolescents (Cosi et al., 2008; Hartmann et al., 2011; Li & Chen, 2007; von Diemen et al., 2007) and among elderly (Tamam, Bican, & Keskin, 2014). BIS‐11 has also been used among PD patients Antonini et al, 2011; Smulders et al, 2014 among patients with depression (Lu et al., 2012; reviewed in Saddichha & Schuetz, 2014) as well as in combinations of both (Fonoff et al., 2015). ICDs have also been studied (binge eating: [Akkermann et al, 2010], substance dependence: [Gülec et al., 2008], prison inmates: [Patton et al., 1995], elderly with ICDs: [Tamam et al., 2014]).…”
Section: Discussionmentioning
confidence: 99%
“…(2009) suggest that the BIS‐11 should be viewed as a standard point of reference in research on impulsiveness. The scale has begun to be used in studies of impulsivity among samples of Parkinson patients (Antonini et al., 2011) but has, to the best of our knowledge not been used in medication‐overuse headache or other chronic headaches.…”
Section: Introductionmentioning
confidence: 99%
“…ИКР при БП включают игрома-нию (патологический геймблинг), ониоманию (компуль-сивный шопинг), навязчивые бессмысленные действия (пандинг), гиперсексуальность, гиперфагию (патологиче-ское переедание) и дофаминовый дизрегуляционный син-дром. Частота ИКР у пациентов с БП, не получающих лече-ние, не отличается от таковой в общей популяции [43], в то время как у лиц, находящихся на противопаркинсониче-ской терапии, ИКР встречаются в большом числе случаев [44]. Таким образом, важную роль в развитии данного вида расстройств играют дофаминергические средства, особенно прием агонистов дофаминовых рецепторов и препаратов леводопы.…”
Section: о б з о р ыunclassified
“…Studies addressing the relation between OCS and ICDs in PD are even scarcer. Antonioni and coworkers [22] tested this association and found that the ICD score was not significantly correlated to the OCS score, but rather with depression. Furthermore, the association of specific types of ICD with OCS has not been addressed.…”
Section: A Connection Between Icds Andmentioning
confidence: 99%
“…Furthermore, ICDs have also been described in patients receiving dopaminergic drugs for disorders other than PD, such as restless legs syndrome [20] and prolactinoma [21]. However, most patients under high doses of dopaminergic drugs do not develop ICDs [10,11], and these disorders have also been described in drug-naïve PD patients [22], which suggests that other factors must be at play. The effect of deep brain stimulation (DBS) treatment for PD further suggests that factors other than dopaminergic drugs could contribute for the development of ICDs in PD [23,24].…”
Section: Introductionmentioning
confidence: 99%